Median Arcuate Ligament Syndrome (MALS), also known as Dunbar syndrome – pathophysiology. diagnosis and treatment: a narrative review - Baran, Adrian; Maciejowski, Michał; Zdaniewicz, Mateusz; Adamiak, Jakub; Czyżak, Bartłomiej; Olejnik, Agnieszka; Kiereta, Kacper; Cichowska, Zuzanna; Bacik, Małgorzata; Głodowska, Klaudia (Journal of Education, Health and Sport, 2026)
Introduction and purpose: Median arcuate ligament syndrome (MALS), also known as Dunbar syndrome, is a rare disorder caused primarily by compression of the celiac axis by the median arcuate ligament and diaphragmatic crura. This disorder usually causes weight loss, nausea, vomiting, and postprandial epigastric pain. Because the diagnosis of MALS requires ruling out other conditions, as it lacks specific criteria, it still presents as a diagnostic and therapeutic challenge. This narrative review was conducted to consolidate current knowledge of this syndrome, focusing on its etiology, diagnosis, and therapeutic strategies. A brief description of the state of knowledge: MALS remains a controversial diagnosis, which can only be established after excluding all other potential causes of abdominal pain. Nowadays, the primary first-line diagnostic tool is Doppler ultrasound, which typically reveals elevated peak systolic velocity during expiration; however, in most cases, the diagnosis must be confirmed by computed tomography angiography (CTA) or, in some cases, magnetic resonance angiography (MRA). Surgery may be performed using an open approach or a minimally invasive technique, including laparoscopic or robot-assisted methods. Summary: While MALS has been acknowledged for decades, standardized diagnostic and treatment protocols are still incomplete. Multiple treatment options exist, with selection often based on the patient's specific clinical presentation and preferences. Many concerns, including the long-term quality of life following robotic decompression and whether vascular reconstruction is needed in cases of persistent stenosis, still need thorough prospective studies.